Impact of Normoglycemia in Reducing Microvascular Complications in Patients with Type 2 Diabetes: A Follow-Up Study - Ishibashi, Fukashi; Tavakoli, Mitra (Frontiers in Endocrinology, 2018)
Aims: Hyperglycemia is associated with increased risk of microvascular complications in patients with type 2 diabetes. The aim of present study was to investigate whether reduction of the levels of HbA1c by tight glycemic control (GC) decreases the rate of microvascular complications and improves the neurological measures in patients with type 2 diabetes. Methods: Detailed clinical and neurological examinations including corneal confocal microscopy (CCM) were performed in 141 Japanese patients with type 2 diabetes and 60 age-matched control subjects at baseline and follow-up with GC for 4 years. Patients were stratified according to mean HbA1c level during follow-up into good (HbA1c <53.0 mmol/mol, mean; 47.5 mmol/mol), fair (53.0 mmol/mol ≤HbA1c <58.5 mmol/mol, mean; 55.6 mmol/mol), and poor (HbA1c ≥58.5 mmol/mol, mean; 68.9 mmol/mol) GC groups with similar HbA1c levels at baseline (84.5–88.2 mmol/mol). Results: At baseline CCM revealed significant nerve fiber damage in all patients compared to controls. The interval changes in most corneal nerve fiber (CNF) parameters and neurophysiological functions were significantly related with mean HbA1c levels during follow-up. Interestingly the baseline HbA1c level did not impact on neurological functions at follow-up. Interval changes in neuropathy outcomes were associated with mean clinical factors during follow-up and hypoglycemic strategies. Good GC improved all nerve functions, including CNF branch density and bead, but not length and main fiber density. Fair GC deteriorated some nerve functions. Poor GC compromised all neuropathy outcomes. Irrespective of GC levels retinopathy increased after follow-up period, while nephropathy decreased. Conclusion: This study showed that the tight GC was beneficial just for nephropathy among microvascular complications. Despite strict GC, the retinopathy progressed in patients with type 2 diabetes. Glucose control did not improve neurophysiological and corneal nerve measurements unless near-normoglycemia was reached.